2013
DOI: 10.3389/fnbeh.2013.00154
|View full text |Cite
|
Sign up to set email alerts
|

Variable delay-to-signal: a fast paradigm for assessment of aspects of impulsivity in rats

Abstract: Testing impulsive behavior in rodents is challenging and labor-intensive. We developed a new behavioral paradigm—the Variable Delay-to-Signal (VDS) test—that provides rapid and simultaneous assessment of response and decision impulsivity in rodents. Presentation of a light at variable delays signals the permission for action (nose poke) contingent with a reward. 2 blocks of 25 trials at 3 s delay flank a block of 70 trials in which light is presented with randomly selected 6 or 12 s delays. Exposure to such la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 33 publications
(52 reference statements)
0
36
0
Order By: Relevance
“…We observed that KET-multiple exposure abolished the increase in the rate of PR (PR/minute) that is generally observed in the last block [3 s (f)] after the long-delay trials (6 and 12 s; Leite-Almeida et al, 2013). This effect was preserved in control animals.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…We observed that KET-multiple exposure abolished the increase in the rate of PR (PR/minute) that is generally observed in the last block [3 s (f)] after the long-delay trials (6 and 12 s; Leite-Almeida et al, 2013). This effect was preserved in control animals.…”
Section: Discussionmentioning
confidence: 53%
“…To further explore the possibilities offered by VDS in the characterization of impulsivity and according to our previous studies (Leite-Almeida et al, 2013), we partitioned each delay block into 500 ms intervals (Figures 3D–K). This analysis confirmed our previous data showing a decrease of PR for the KET animals when compared with CONT animals (delay: F (3,112) = 10.44, P < 0.0001; exposure to ketamine: F (1,112) = 14.73, P = 0.0002; Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have compared alternative paradigms to the 5CSRTT, however a recent study by Leite-Almeida et al (2013) showed that impulsive responding on their novel Variable Delay-to-Signal task correlated with impulsivity during early stages of 5CSRTT training (although not when attentional load increased). It is important to note the 5CSRTT is very useful for measuring impulsive behaviour but this has not been a priority in developing the SDT.…”
Section: Discussionmentioning
confidence: 99%